Does tooth loss have an emotional effect? A cross-sectional and comparative study on nondenture wearers and complete denture wearers - Md. Shakeel Anjum; M Monica; K Yadav Rao; P Parthasarathi Reddy; Irram Abbas Hameed; M Jyothi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Teeth play various functional and esthetic roles. As any part of the body, even teeth loss gives one the feeling of being handicapped showing a negative impact on emotions. Sometimes, few people think that having 32 teeth and losing a few among them will not make a difference. Aim: To assess and compare the emotional effects due to loss of natural teeth in complete denture wearers and nondenture wearers. Materials and Methods: A hospital-based survey was conducted on complete denture wearers and nondenture wearers who were attending the outpatient department in a dental hospital for 2 months using a pretested, self-administered questionnaire. Results: Among them who were surveyed, 65.75% agreed accepting the tooth loss is difficult, only 30.13% felt that loss of teeth affected their self-confidence (P = 0.094), about 80.82% reported that natural teeth loss affected their eating efficiency, and 57.53% of them found it difficult while speaking to others. There was a significant difference between denture wearers and nondenture wearers when asked whether loss of teeth affected their looks, eating efficiency, and speaking difficulties (P = 0.000). Conclusion: Even though the majority of them found it difficult in accepting tooth loss, it did not affect their self-confidence majorly; however, most of them found functional difficulties with loss of natural teeth.